2017
DOI: 10.3136/nskkk.64.549
|View full text |Cite
|
Sign up to set email alerts
|

Time-Intensity Flavor Profile of Commercial Strawberry Jams Available in the Japanese Market

Abstract: Time-intensity (TI) assessment was applied for sweetness, sourness and strawberry flavor of commercial strawberry jams. Ten strawberry jams were selected out of 51 products available in Japan. The selected jams covered a wide range of soluble solids concentrations, colors and sensory characteristics. Eleven trained panelists evaluated the sensory attributes of each sample for 90 or 120 seconds using a sliding TI switch. The obtained average TI curves and the TI parameters demonstrated the characteristics of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…However, the strawberry flavor ( I max , AUC, and T tot ) increased as R 60 values increased. This is consistent with the results of the commercial strawberry jam (Kurotobi et al, 2017). As the aromatic components are the same for the samples with the same composition, the correlation is considered lower than that for the commercially available strawberry jam.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…However, the strawberry flavor ( I max , AUC, and T tot ) increased as R 60 values increased. This is consistent with the results of the commercial strawberry jam (Kurotobi et al, 2017). As the aromatic components are the same for the samples with the same composition, the correlation is considered lower than that for the commercially available strawberry jam.…”
Section: Discussionsupporting
confidence: 93%
“…We suggest that the decreased perception of sweetness was due to the firm texture of the jam (it was difficult to spread), and the samples contained a wide range of soluble solid concentrations. However, we used the same protocol as that in our previous study (Kurotobi et al, 2017), which indicates that soluble solids and sugar composition are the same. Therefore, the results suggested that model strawberry jams exhibited lower correlation between SM 165 values (LST) and each sweetness parameter than that for commercial strawberry jams.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The taste strength is generally low in the initial stage, increases in the middle stage, and decreases in the final stage. (21)(22)(23) On the basis of these findings, it is necessary to develop a method of evaluating the change in taste during the chewing process while ensuring consistency with the results of the taste sensor measurement.…”
Section: Resultsmentioning
confidence: 99%